Seed Yield and Quality of Late Season Jute (Corchorus olitorius L.) Seed as Influenced by Plant Growth Regulators (The Agriculturists, 2018)
An experiment was conducted at Jute Research Regional Station (JRRS) of Bangladesh Jute Research Institute (BJRI), Kishoreganj during August 2009 to January 2010 to determine the effect of different plant growth regulators on seed yield and quality of olitorius jute using late jute seed production technique. The experiment was laid out in a randomized complete block design (RCBD) with four replications. Seven growth regulators with different brand names such as Bionik, Litosen, Okozim, Mirakulan, Planovit, Flora and Yield were used in the experiment. All the yield contributing characters increased due to the application of growth regulators over the control. The highest seed yield (2.91g/plant) was obtained with Bionik which was followed by Mirakulan> Okozim> Litosen> Planovit> Yield> Flora> control. The highest of 33.49% seed yield was found in Bionik over control.  In terms of quality of seeds, the plant growth regulator `Bionik’ performed the best.The Agriculturists 2017; 15(2) 115-121